Words and expressions in movies: Indonesian English as a foreign language students’ reflection - Choiril Anwar; Dhobith Anis Murtadho (NOTION: Journal of Linguistics, Literature, and Culture, 2023)
This study was aimed to find out the students’ reflection on the words and expressions found in English-spoken Hollywood movies, more particularly Thor Ragnarok. This descriptive quantitative study was conducted via discord. The population of the study was SMAN 2 Semarang students and the samples were the eleventh-grade students who watch Thor Ragnarok movie. The data were collected through questionnaire. The result of analysis showed that there are many students who feel their English are improved by watching Hollywood movies but they also absorb the culture like kinds of impolite words and expressions. After all, the results can give implication for how students need to study on absorbing western cultures correctly and using the words and expressions properly in appropriate ways.